Elemental diet for refractory atopic eczema. Issue 1 (January 1991) - Devlin, J; David, T J; Stanton, R H
Abstract : A total of 37 children with refractory wide-spread atopic eczema were treated with an antigen avoidance regimen comprising hospitalisation, exclusive feeding with an elemental formula for a median duration of 30 days, and measures to reduce exposure to pet and dust mite antigens at home. After the initial period of food exclusion, food challenges were performed at intervals of seven days, and the patients followed up for at least 12 months. Ten of the children (27%) either failed to respond to the regimen or relapsed within 12 months. Improvement in the eczema was seen in 27/37 (73%) patients, by discharge from hospital their disease severity score had fallen to a median of 27% of the pretreatment figure, and only 3/27 required topical corticosteroids. There were no clinical or laboratory findings which could be used to predict the outcome. Drawbacks to the regimen were prolonged hospitalisation (median 70 days), a fall in body weight and serum albumin concentration, and a risk of anaphylactic shock (4/37 cases). A strict antigen avoidance regimen may be associated with improvement of atopic eczema where conventional treatments have failed.